Social reforms and women’s empowerment in 19th-century India - Chauhan, Anita (Journal of Social Review and Development, 2023)
The nineteenth century was an era in which gender relations underwent a major transformation in Indian social history. During this period of Indian society, various archaic customs such as sati, child marriage, female infanticide, the prohibition of widow remarriage, the denial of women's education, and rigid patriarchal structures characterized much of the way of life. British colonial rule, the diffusion of Western education and the rise of other social and religious reform movements produced the right conditions for social changes. Advocates of women’s rights and education were prominent reformers like Raja Ram Mohan Roy, Ishwar Chandra Vidyasagar, Jyotirao Phule, Savitribai Phule, Pandita Ramabai and Swami Dayanand Saraswati. Reform reforms like women’s education and advocacy led to early reform movements which paved the way women empowerment in India that promoted female education, widow remarriage, sati abolishment and social equality. This paper analyses the significance and reaches of the nineteenth-century social reforms on women's empowerment in India. It also explores the limitations and ongoing impact of these reforms on modern Indian society.